Percentage Points For Testing Two-Sample Compound Symmetry (2023)
The exact null distribution of the likelihood ratio statistic for simultaneous testing the equality of covariance matrices and compound symmetry of two m variate Gaussian models has been obtained and percentage points for m ≤ 7 have been computed. Inverse Mellin transform and calculus of residues have been used to derive these results.